2006
DOI: 10.3732/ajb.93.8.1125
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variation in growth, form, and survival in dwarf and normal‐stature pitch pines (Pinus rigida, Pinaceae) in long‐term transplant experiments

Abstract: Determining the relative contributions of genetic and environmental factors to phenotypic variation is critical for understanding the evolutionary ecology of plant species, but few studies have examined the sources of phenotypic differentiation between nearby populations of woody plants. We conducted reciprocal transplant experiments to examine sources of variation in growth rate, form, survival, and maturation in a globally rare dwarf population of pitch pine (Pinus rigida) and in surrounding populations of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…In addition, Kurahashi et al (1992) reported that the reproduction of high‐elevation progeny of A. sachalinensis began at a younger age than that of low‐elevation progeny. Sakai et al (2003) and Fang et al (2006) also found that both Abies mariesii and Pinus rigida trees derived from high‐elevation populations reproduced at an earlier age than those from low‐elevation populations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, Kurahashi et al (1992) reported that the reproduction of high‐elevation progeny of A. sachalinensis began at a younger age than that of low‐elevation progeny. Sakai et al (2003) and Fang et al (2006) also found that both Abies mariesii and Pinus rigida trees derived from high‐elevation populations reproduced at an earlier age than those from low‐elevation populations.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies using common garden and reciprocal transplant experiments have demonstrated that ecotypic differentiation along an altitudinal gradient can occur within a continuous population (Conkle 1973;Harry et al 1983;Oleksyn et al 1998;Wu & Ying 2004;Kitzmiller 2005). However, other researchers have failed to detect local adaptation along an altitudinal gradient (Reich et al 1996;Isik & Kara 1997;Nakagawa et al 2003;Fang et al 2006). To determine local adaptation to elevation, ecological and/or physiological mechanisms must be compared between local and nonlocal populations (Oleksyn et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, plasticity might be of greater importance as an adaptive strategy in trees and woody plants compared with short-lived plant species (Willson, 1983) such that long-lived species might exhibit plasticity in both vegetative (Chambel et al, 2005) and reproductive traits like size at reproduction and reproductive investment. The few studies published on long-lived species highlight strong selection on the threshold size at first reproduction and the allometry of reproduction, leading to genetic differentiation at large spatial scales (Thomas, 1996;Matziris, 1997;Niklas & Enquist, 2003;Climent et al, 2008;Santos-del-Blanco et al, 2010) and promoting phenotypic plasticity in life histories at local scales (Fang et al, 2006). Despite consistent predictions of plasticity in the threshold size of reproduction, little is known about the costs of plasticity in terms of final reproductive output relative to vegetative size (Roff, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Hypotheses regarding plasticity of threshold size for reproduction have been addressed in plants only in few cases Bonser et al, 2010), in contrast with predictions of the high relevance of this type of plasticity . However, evidences pointing at this phenomenon are common through the literature (Nagy & Proctor, 1997;Fang et al, 2006). We relied on two natural environments to test our hypothesis, which also allowed us to study local adaptation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, plasticity might be of greater importance as an adaptive strategy in trees and woody plants compared with short-lived plant species (Willson, 1983) such that long-lived species might exhibit plasticity in both vegetative (Chambel et al, 2005) and reproductive traits like size at reproduction and reproductive investment. The few studies published on long-lived species highlight strong selection on the threshold size at first reproduction and the allometry of reproduction, leading to genetic differentiation at large spatial scales and promoting phenotypic plasticity in life histories at local scales (Fang et al, 2006). Despite consistent predictions of plasticity in the threshold size of reproduction, little is known about the costs of plasticity in terms of final reproductive output relative to vegetative size .…”
Section: Introductionmentioning
confidence: 99%